Industrial Crops and Uses - Singh, Bharat P (CABI, 2014)
The 21st century promises to be the period of a new industrial revolution in which the criteria for the selection of raw materials will be decided by their renewable nature and environmentally friendly accessibility, in contrast to the preceding century in which petroleum, a depleting raw material source and cause for multiple health and environmental concerns, dominated the indus- trial scene. The industries of the future will rely increasingly on resources such as the wind and the sun, which previously have been untapped, and old sources of raw materials such as plants, which were abandoned during the last century in favour of petroleum. Plants, because of their potential to yield a wide range of products, their renewable nature and their positive environ- mental impacts, are destined to play a key role in this new industrial economy. These products will include liquid fuels, chemicals, lubricants, plastics, paints, building materials, insecticides and pharmaceuticals, to name a few. In addition, plants will play a crucial role in the reclamation of soil, water and air polluted by the petroleum-based industries. How fast and by how much industries based on plant raw material will develop depends on a multitude of factors, such as research into crop production and processing, infrastructure development for plant-based industries, the cost competitiveness of bio-based products against petroleum-derived products, consumer demand and political support.